Study on the Influence of Different Soil Stratification Schemes on Soil Freezing and Thawing Process - Zisha LIU; Shihua LÜ; Yiqun BAO (Gaoyuan qixiang)
In this paper， the BCC_AVIM land model and encrypted observation data are used to evaluate the simulation performance of different soil stratification schemes on soil temperature and humidity.The results indicate that the encryption scheme has the best simulation performance.In the BCC_AVIM land model， the soil layer is defined as ten layers and linearly interpolate the depth of each adjacent node to obtain a new 20-layer scheme， referred to as the encryption scheme in this paper.The soil stratification scheme with 20 soli layers in the reference model CLM5.0 is also applied to the BCC_AVIM land model， which is called CLM5.0 scheme in this paper.Comparing the simulation results of the soil stratification scheme before and after improvement with the encrypted observation data， it shows that： （1） The encrypted observation data and the original observation data can well reflect the changing trend of soil temperature and humidity at the whole vertical level， but for the soil freezing period， the encrypted observation data can better depict the temperature change of shallow soil and the humidity change of deep soil.（2） For the soil temperature and humidity during the freezing period， the simulation performance of the encryption scheme and CLM5.0 scheme show improvements compared with the original scheme.The encryption scheme is closest to the measured temperature and humidity data’s numerical values and amplitude changes.Furthermore， the encryption scheme is more reasonable in determining freezing time in the soil’s shallow and middle layers.（3） For the soil temperature and humidity during ablation， the simulation performance of the encryption scheme and CLM5.0 scheme are enhanced compared with the original scheme.After the shallow and middle soil layers enter the ablation period， the simulated and measured data of soil temperature and humidity by the encryption scheme are closer to the numerical values and curve trends.